Balanced Ionic‐Electronic Conductors Enabling Organic Electrochemical Memristors - Yani Wang; Linlin Pang; Hengyi Ma; Mingyu Liu; Yongchao Jia; Yu Wei; Shangzhi Chen; Hengda Sun; Yuanchun Zhao; Kai Xu (SmartMat, 2025)
ABSTRACT Despite great advancements in organic mixed ionic‐electronic conductors (OMIECs), their applications remain predominantly restricted to three‐electrode organic electro‐chemical transistors (OECTs), which rely on an additional electrolyte layer to balance ionic and electronic transport, resulting in indirect coupling of charge carriers. While direct coupling has the potential to greatly simplify device architectures, it remains underexplored in OMIECs due to the inherent imbalance between electronic and ionic conductivities. In this study, we introduce a straightforward approach to achieve balanced OMIECs and employ them as channel materials in two‐electrode organic electrochemical memristors. These devices provide clear evidence of direct coupling between electronic and ionic carriers and exhibit exceptional performance in synaptic device applications. Our findings offer new insights into charge carrier transport mechanisms in OMIECs and establish organic electrochemical memristors as a promising new class of organic electronic devices for next‐generation neuromorphic applications.